CONSUMPTION OF PREBIOTIC SOURCES SIGNIFICANTLY AFFECTS CHILDREN HEIGHT IN A STUNTING LOCUS VILLAGE IN BOGOR REGENCY INDONESIA: Konsumsi Sumber Prebiotik Signifikan Berpengaruh terhadap Tinggi Badan Anak di Desa Lokus Stunting Kabupaten Bogor Indonesia - Nadiyah; Lintang Purwara Dewanti; Jeallyza Muthia Azra; Intan Permatasari; Putri Ronitawati (Poltekkes Kemenkes Yogyakarta, 2025)
Stunting is a condition of growth failure in children that occurs due to chronic nutrient deficiencies for a long time, especially during the first 1000 days of life. Children are classified as stunted if the length/height z-score-for-age is <-2 SD. Stunting can occur due to poor gastrointestinal conditions. Prebiotics and probiotics play an important role in helping to maintain gastrointestinal health. The purpose of this study was to analyze the relationship between the consumption of prebiotic and probiotic food sources and the z-score of height/length for age. This cross-sectional study included 100 children aged 6-59 months in the stunting locus village of Bogor Regency. Height/length data were obtained using a stadiometer and infant to meter. Assessment of food consumption of prebiotic and probiotic sources was conducted through interviews using the Semi Quantitative-Food Frequency Questionnaire form. Bivariate test used Pearson correlation test and multivariate test used multiple linear regression test. The data showed that 48% of children were stunted, and 52% were normal. Bivariate test showed correlations of food consumption of prebiotic sources (r =0.274, p=0.006) and probiotics (r=0.264, p=0.008) with height/length z-score. Multivariate test results showed that consumption of prebiotic sources influenced length/height z-score for age (?=0.007, 95%CI: 0.002-0.011, p=0.003). Consumption of prebiotic food sources in children can improve the z-score of height-for-age.